Effects of MyTeachingPartner–Math/Science on Teacher–Child Interactions in Prekindergarten Classrooms. Issue 1 (2nd January 2016) - Vick Whittaker, Jessica; Kinzie, Mable B.; Williford, Amanda; DeCoster, Jamie
ABSTRACT: Research Findings: This study examined the impact of MyTeachingPartner–Math/Science, a system of math and science curricula and professional development, on the quality of teachers' interactions with children in their classrooms. Schools were randomly assigned to 1 of 2 intervention conditions (Basic: curricula providing within-activity, embedded teacher supports; Plus: curricula plus implementation support via online resources and in-person workshops) or to a Business-as-Usual (BaU) control condition. Results showed that teachers in the Basic and Plus conditions showed higher levels of Instructional Support and Facilitation of Mathematical and Scientific Thinking. Teachers in the Basic condition also showed higher levels of Emotional Support compared with teachers in the BaU condition. We did not find any significant differences between teachers' interactions in the Basic and Plus conditions. Practice or Policy : Children are entering kindergarten unprepared in the areas of mathematics and science, largely as a result of inadequate exposure to early experiences and high-quality interactions in these domains. The results of this study suggest that providing teachers with math and science curricula that include embedded teacher supports can have an impact on the quality of their math and science instruction.